A comparison of linear and integer linear programming for the profit optimization in bakery production: A case study at Temptlicious Enterprise / Diana Sirmayunie Mohd Nasir ... [et al.] - Mohd Nasir, Diana Sirmayunie; Hamdan, Nur Najihah; Shafii, Nor Hayati; Mohamad Nor, Nor Azriani (UiTM Cawangan Perlis, 2022)
Nowadays, the bakery industry is widely spread and famous because it can be run by a small industry or a large industry. Seeing as bakery businesses, especially small industries prefer to allocate scarce resources through trial and error to maximize profit. As a result, the company has had difficulty allocating scarce resources, affecting gross profit and gross profit margin (GPM). As a consequence, the goals of this study were (i) to determine the total number of selected products that Templicious Enterprise should produce, (ii) to compare final results using Linear Programming (LP), Integer Linear Programming (ILP), and trial-and-error methods and (iii) to find out the limits of the maximum and minimum for each type of product using sensitivity analysis. The LP and ILP methods are calculated manually and using QM for Windows. As a result, it shows that the Templicious Enterprise should produce a total of one cycle (3 units) of standard pavlova, three cycles (24 units) of superbaby pavlova and one cycle (2 units) of personal pavlova for a total profit of RM 446.99. The result was obtained using ILP, and lastly, it shows that if prices rise, the Temptlicious Enterprise will have to raise the price of the pavlova they make to avoid making a loss.